A genetic mouse model with postnatal Nf1 and p53 loss recapitulates the histology and transcriptome of human malignant peripheral nerve sheath tumor. Issue 1 (10th September 2021) - Inoue, Akira; Janke, Laura J; Gudenas, Brian L; Jin, Hongjian; Fan, Yiping; Paré, Joshua; Clay, Michael R; Northcott, Paul A; Hirbe, Angela C; Cao, Xinwei
Abstract: Background: Malignant peripheral nerve sheath tumors (MPNST) are aggressive sarcomas. Somatic inactivation of NF1 and cooperating tumor suppressors, including CDKN2A/B, PRC2, and p53, is found in most MPNST. Inactivation of LATS1/2 of the Hippo pathway was recently shown to cause tumors resembling MPNST histologically, although Hippo pathway mutations are rarely found in MPNST. Because existing genetically engineered mouse (GEM) models of MPNST do not recapitulate some of the key genetic features of human MPNST, we aimed to establish a GEM-MPNST model that recapitulated the human disease genetically, histologically, and molecularly. Methods: We combined 2 genetically modified alleles, an Nf1 ; Trp53 cis-conditional allele and an inducible Plp-CreER allele (NP-Plp), to model the somatic, possibly postnatal, mutational events in human MPNST. We also generated conditional Lats1 ; Lats2 knockout mice. We performed histopathologic analyses of mouse MPNST models and transcriptomic comparison of mouse models and human nerve sheath tumors. Results: Postnatal Nf1;Trp53 cis-deletion resulted in GEM-MPNST that were histologically more similar to human MPNST than the widely used germline Nf1;Trp53 cis-heterozygous (NPcis) model and showed partial loss of H3K27me3. At the transcriptome level, Nf1;p53- driven GEM-MPNST were distinct from Lats -driven GEM-MPNST and resembled human MPNST more closely than do Lats- driven tumors. Conclusions: The NP-Plp model recapitulates human MPNST genetically, histologically, and molecularly.